Factors controlling the isotopic partitioning between soil evaporation and plant transpiration: Assessment using a multi-objective calibration of SiSPAT-Isotope under controlled conditions - Rothfuss, Youri; Braud, Isabelle; Le Moine, Nicolas; Biron, Philippe; Durand, Jean-Louis; Vauclin, Michel; Bariac, Thierry (Journal of hydrology (Amsterdam), 2012)
► Controlled conditions experiments and deterministic models are complementary. ► We perform a multi-objective calibration of the SiSPAT-Isotope SVAT model. ► Model parameters distributions are inferred from the calibration. ► We simulate the evolutions of soil isotopic compositions and root water uptake. ► We provide guidelines for partitioning evapotranspiration in the field. Stable isotopes of water (18O and 2H) are tracers of ecosystem processes and in particular of water vapour sources. They have been substantially used for evapotranspiration (ET) studies. Data gathered during a series of soil monoliths experiments under fully controlled conditions allowed the partitioning of ET fluxes into soil evaporation (Ev) and plant transpiration (Tr) from isotopic measurements along growth of a tall fescue cover. These data were used to calibrate SiSPAT-Isotope, a 1D Soil–Vegetation–Atmosphere Transfer (SVAT) model coupled with a module for isotopic transport in the soil and the atmosphere. For this, the soil isotopic module was extended to take into account plant water uptake by roots and the model was modified so that it could be constrained with collected input data (e.g. ET flux). The multi-objective calibration method allowed determining narrowed probability distributions for soil, plant and isotopic parameters of which some are currently debated and/or typically not measured in the field (e.g. kinetic fractionation factor during soil evaporation). Comparisons between simulation results corresponding to the “best compromise” parameter set with data (i.e. soil water pressure and contents, soil temperatures and heat fluxes, soil isotopic compositions, and root extraction depths) were provided to show the consistency of the calibration method. Guidelines were provided for the determination of the isotopic composition of evaporation in the field: we could emphasize the importance of values used for the kinetic fractionation factor and the impact of the heights at which atmospheric variables (air relative humidity and temperature, isotopic composition of atmospheric water vapour) are measured in the field.